The use of inpatient goal planning in a regional burns centre: A thematic analysis of staff and patient experiences. Issue 1 (February 2023) - Watkins, Helen; Hughes, Olivia; Jones, Lowri; Tate, Laurie; Khela, Mariam Mouris; Hurrell, Chloe
Highlights: Goal planning may be successfully used in the rehabilitation of injured patients being treated in a burns centre. Goal planning was generally well-received and was reportedly found useful by patients and staff involved in this study. Staff should be allocated time and resources to integrate the strategy of goal planning into rehabilitation. Abstract: Background: Rehabilitation from a burn or related injury can be a lengthy and painful process. Objectives: The present study explored the experiences of staff and patients of inpatient goal planning used on a rehabilitation ward within a regional burns centre. Design: A qualitative study using semi-structured interviews. Setting: Patients and staff were recruited from The Welsh Centre for Burns and Plastic Surgery, Morriston Hospital, Swansea, South Wales, UK. Participants: Twelve participants were recruited and interviewed in two phases. Phase one included six staff members who had been involved in delivering goal planning sessions and phase two included six former inpatients who had participated in goal planning during their rehabilitation in hospital. Results: Three main themes were identified for staff: benefits for patients and families, process and structure and challenges of the process. For patients, the three main themes identified were: role of goal planning in rehabilitation, tailoring the programme around the patient and encountering challenges. Conclusions: Findings from the narratives of staff and patients suggest the use of goal planning in inpatient recovery and rehabilitation in a burns centre is very beneficial. Although challenges were reported, this investigation yields potential for goal planning to be a successful rehabilitation strategy.